Energy performance certificates – Informing the informed or the indifferent?. (December 2017) - Olaussen, Jon Olaf; Oust, Are; Solstad, Jan Tore
Abstract: Energy Performance Certificates (EPCs) are intended to provide tenants and buyers with reliable information about the energy performance of buildings. As improved energy performance may increase building sale prices and rents, the EPCs are supposed to generate incentives for owners to invest in energy efficiency. The empirical evidence for a price premium associated with energy labels is, however, inconclusive and partly contradictory. By utilizing data from the Norwegian housing market, we reproduce the positive price premium effect found in earlier studies. However, when we check these results by taking advantage of the fact that the introduction of a mandatory energy certification system represents a quasi-natural experiment, we find no evidence of a price premium. On the contrary, we present evidence that there is no effect of the energy label itself. Highlights: We study house prices before and after introduction of energy performance certification. Houses with better energy certification are sold for higher price. However, these houses were sold for higher price even before the certification existed. We find no price premium associated with energy performance certificates. Recommend to reevaluate the energy performance certification system for buildings.